(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine the functional outcome of dynamic condylar screw in the treatment of unstable proximal femoral fractures in adult patients. Methods: This descriptive study was conducted in Department of Orthopedics, Bolan teaching hospital Quetta from January 2017 to December 2018.All adults patients of proximal femoral fractures meeting the inclusion criteria were fixed with dynamic condylar screw(DCS).Post operatively functional outcome was assessed Harris Hip Score. Results: We operated 147 patients with mean age of patients 54.26 ± 5.14 years. The male to females ratio was 1.94:1. Post operative functional outcome was excellent in 69(46.4%) patients, good in 58(39.45%), fair in 12(8.16%) and poor in 8(5.44%) patients. Post operatively Harris Hip score was excellent(>90) in 69(46.94%) patients, Good score ( 80-89 ) in 58 (39.45%) patients ,Fair score(70-79) in 12(8.16%) patients and poor score(<70) in 8(5.44%) patients.Non union was reported in only 3(2.04%) patients. Conclusion: Unstable proximal femoral fractures fixed with Dynamic Condylar Screw(DCS) results in excellent and good functional outcome in majority of patients. We therefore recommend DCS as a suitable alternative to intramedullary implants to treat subtrochanteric fractures.